Distribusi dalam Perspektif Muhammad Baqir Al-Sadr (Equilibrium: Jurnal Ekonomi Syariah, 2020)
This study aims to know the Muhammad Baqir Al-Sadr ideas about the distribution and analyze the relevance of Baqir Al-Sadr's thinking in the current economic context. This literary research is classified as a study of figures who studies Baqir Al-Sadr's thoughts on the concept of distribution. This study found that Baqir Al-Sadr's thoughts contradict with other capitalist thoughts. Conventional economic thinkers argue that economic problems arise due to resource scarcity, but Baqir Al-Sadr believes that economic problems arise due to unequal distribution. Fairness of distribution in the context of zakah is very relevant. The relevance of wealth distribution is the practice of the zakah system through BAZ and LAZ. They cannot play a maximal role in changing the position of mustahiq-muzakki if the state is not present. The presence of the state has an important role in creating and maintaining social justice. Baqir Al-Sadr's thoughts are written in the monumental work of Iqtisaduna which discusses the theory of production and distribution.